5.1k views
5 votes
HELP PLEASE!! I DONT UNDERSTAND!!!!!!!!!! THANKS SO MUCH

HELP PLEASE!! I DONT UNDERSTAND!!!!!!!!!! THANKS SO MUCH-example-1
User Valdemar
by
5.2k points

1 Answer

2 votes

Hello, please consider the following.

We will multiply the numerator and denominator by


4+√(6x)

to get rid of the root in the denominator.

First of all, we cannot divide by 0, right? So, we need to make sure that the denominator is different from 0.


4-√(6x) =0<=>√(6x)=4\\\\\text{Take the square}\\\\6x=4^2=16\\\\x=(16)/(6)=(8)/(3)

We need to take any x real number different from 8/3 then and simplify the expression.

Let's do it!


\begin{aligned}(4)/(4-√(6x))&amp;=(4(4+√(6x)))/((4+√(6x))(4-√(6x)))\\\\&amp;=(4(4+√(6x)))/((4^2-√(6x)^2))\\\\&amp;=(4(4+√(6x)))/((16-6x))\\\\&amp;=(2(4+√(6x)))/((8-3x))\\\\&amp;\large \boxed{=(8+2√(6x))/(8-3x)}\end{aligned}

Thank you

User Jonny
by
4.4k points